Monitoring therapeutic proton beams with LGAD silicon detectors. (1st November 2022) - Vignati, A.; Abujami, M.; Bersani, D.; Borghi, G.; Centis Vignali, M.; Data, E.; Ficorella, F.; Galeone, C.; Garbolino, S.; Giordanengo, S.; Hammad Ali, O.; Martì Villarreal, O.A.; et al.
Abstract: The University and the National Institute for Nuclear Physics of Torino are developing LGAD-based prototypes for beam monitoring in proton therapy. The direct measurement of single beam particles could overcome some features of currently used ionization chambers, such as slow charge collection and reduced sensitivity, which limit the implementation of advanced delivery techniques (e.g. rescanning). LGAD strip sensors have been designed and produced by Bruno Kessler Foundation (FBK, Trento) specifically for this project. A counter prototype to directly count individual protons at clinical fluence rates (10 6 –10 10 protons/cm 2 ·s) and a telescope system to measure the beam energy with time-of-flight (TOF) techniques are described. Tests of LGAD silicon strip sensors performed on synchrotron and cyclotron beams of therapeutic centers, using a pin-hole ionization chamber for the independent measurement of the particle flux, already showed the possibility to keep the counting error <1% up to a beam fluence rate of few 10 8 protons/cm 2 ·s. The ongoing tests of counting sensors readout by a dedicated fast charge sensitive amplifier chip are reported. The telescope system, made of two sensors at a distance up to 95 cm, allows measuring the beam energy in the clinical range (70–230 MeV) with a maximum deviation of 310 keV in respect to the nominal one, with an uncertainty of 500 keV, thus achieving the prescribed clinical accuracy of 1 mm in the range in water.